Pink money e comunicação: análise das narrativas publicitárias e das interações em pontos de vendas no consumo LGBTI na cidade de Belém - DIAS, Marcio Monteiro (Universidade Federal do Pará, 2019)
This research analyzes the market communication strategies for the LGBTI segment (Lesbian, Gay, Bisexual, Transvestite, Transsexual, Transgender and Intersex), as well as the role of advertising and propaganda as a constructor of meanings and their contributions in the representation and signature of this segment, especially from the contributions of studies on consumption, gender and sexuality, social representations, marketing and communication. In order to do so, we consider the potential for buying and the emergence of discussions on gender and sexuality issues, contextualized in the context of new forms of communication and advertising narratives, based on the observation of some advertising examples directed to the aforementioned public. In addition, it seeks to trace an investigation, in parallel with the scenario experienced in the advertising pieces, with the ways in which the points of sale are receiving and dealing with the diversity of their clients / consumers, current and potential, using an ethnographic study carried out in two shopping malls in the city of Belém - Pará, through a purchase simulation. In this study, the experience of disclosure and purchase is understood not only as an exchange of market and monetary value but as one of the possibilities of debates, experiences and symbolic exchanges that occur with interference and influence of the other aspects that weave the social fabric of life, in certain contexts, such as the construction of stereotypes and social prejudices, understood by the prism of consumption and the social and communicational relations that ensue.